2021
DOI: 10.1002/lno.11691
|View full text |Cite
|
Sign up to set email alerts
|

Daphnia depth selection in gradients of light intensity from different artificial sources: An evolutionary trap?

Abstract: It is well known that artificial light at night alters the natural patterns of light in space and time, which interrupts a variety of physiological processes of individuals, altering their life history and behavioral adjustments. However, much less is known about the effect of artificial light at night on their fitness. We tested the hypothesis that planktonic animals, such as Daphnia spp., are able to correctly assess light intensity‐ and spectrum‐dependent‐mortality risk due to predation by planktivorous fis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 53 publications
1
7
0
Order By: Relevance
“…Mechanistic models predicted that interaction strength scaling depends on both the foraging strategy (e.g. active-capture, sit-and-wait, harvesting) and the spatial dimension in which foraging occurs (2D vs. 3D, 41,50 . In our study, we assessed the thermal sensitivity of the planktivorous sh-Daphnia interface, in which the sh is a typical predator-harvester foraging in a three-dimensional environment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mechanistic models predicted that interaction strength scaling depends on both the foraging strategy (e.g. active-capture, sit-and-wait, harvesting) and the spatial dimension in which foraging occurs (2D vs. 3D, 41,50 . In our study, we assessed the thermal sensitivity of the planktivorous sh-Daphnia interface, in which the sh is a typical predator-harvester foraging in a three-dimensional environment.…”
Section: Discussionmentioning
confidence: 99%
“…Experiments were performed with 6 different pairs of juvenile sh of each of the species. Each pair was maintained in separate aquariums for at least two weeks in an experimental system similar to that used previously 27,50 and have not undergone any prior procedures. We used 6 different pairs sh of each species, because this number provided 144 experiments in total, each experiment on a single pair of sh (2 sh species × 3 temperatures × 6 sh pairs × 4 replicates.…”
Section: Methodsmentioning
confidence: 99%
“… Becker et al., 2013 ; Nguyen and Winger, 2019 ) and enhance their foraging efficiency ( Bolton et al., 2017 ; Fermin and Seronay, 1997 ). From the zooplankton perspective, it has been revealed that its response to the mortality risk in the presence of ALAN may be maladaptive ( Maszczyk et al., 2021 ; Tałanda et al., 2018 ). Direct evidence concerns only the ALAN-dependent effects of fish predation on depth selection behavior of zooplankton populations and communities ( Fermin and Seronay, 1997 ; Maszczyk et al., 2021 ; Moore et al., 2000 ; Springer and Skrzypczak, 2015 ), but neither on the mean body size nor community composition.…”
Section: Introductionmentioning
confidence: 99%
“…From the zooplankton perspective, it has been revealed that its response to the mortality risk in the presence of ALAN may be maladaptive ( Maszczyk et al., 2021 ; Tałanda et al., 2018 ). Direct evidence concerns only the ALAN-dependent effects of fish predation on depth selection behavior of zooplankton populations and communities ( Fermin and Seronay, 1997 ; Maszczyk et al., 2021 ; Moore et al., 2000 ; Springer and Skrzypczak, 2015 ), but neither on the mean body size nor community composition. The aim of our study was to fill this gap by assessing the short-term ALAN-dependent effect of a foraging planktivorous fish lake zooplankton body size and community composition in a preliminary enclosure experiment.…”
Section: Introductionmentioning
confidence: 99%
“…Certain concepts such as "ideal-free distribution" which consider resource availability have been very successful in explaining the vertical distribution of zooplankton under predation risk and other abiotic variables (Maszczyk et al, 2018(Maszczyk et al, , 2021. However, UVR has not specifically been investigated in such models, in spite of the confirmation of UVR being an important driver in the spatial positioning of zooplankton through field observations or population-level experiments (Leech & Williamson, 2001;Rose et al, 2012).…”
mentioning
confidence: 99%